Study on the Permeability of Modified Bentonite Slurry in Landfill - Zenan Zhang; Guozhong Dai; Yanmin Sheng (Advances in Materials Science and Engineering)
The impermeability of cutoff wall is one of the most important factors affecting the life of landfill. Hence, we used sodium carboxymethyl cellulose to modify bentonite and developed a modified bentonite-cement-fly ash antiseepage slurry with a low permeability coefficient. The main material of the slurry is bentonite modified by sodium carboxymethyl cellulose, cement, fly ash, and auxiliary materials such as sodium carbonate and polycarboxylate superplasticizer. The optimal ratio of the basic components of the antiseepage slurry was optimized by the orthogonal test method. The permeability coefficient of the consolidated slurry was determined by a variable head permeameter. The optimal dosage of each component of slurry is 210∼220 kg/m3 cement, 210∼220 kg/m3 bentonite, 1.5∼2.5 kg/m3 sodium carbonate, 1.5∼2.0 kg/m3 sodium carboxymethyl cellulose, 160 kg/m3 fly ash, and 3 kg/m3 polycarboxylate superplasticizer. The 28-day consolidation slurry permeability coefficient is less than 1 × 10−8 cm/s and has a good adsorption effect on the pollutants in landfill leachate.